Identification and Complementation of Frameshift Mutations Associated with Loss of Cytadherence in Mycoplasma pneumoniae - Fisseha, Makda (American Society for Microbiology, 1999)
Mycoplasma pneumoniae cytadherence is mediated by a specialized, polar attachment organelle. Certain spontaneously arising cytadherence mutants (designated class I) lack HMW2, fail to localize the adhesin protein P1 to the attachment organelle, and exhibit accelerated turnover of proteins HMW1, HMW3, and P65. Insertional inactivation of hmw2 by Tn4001 results in a phenotype nearly identical to that of the class I mutants, suggesting that the latter may result from a defect in hmw2. In this study, the recombinant wild-type hmw2 allele successfully complemented a class I mutant when introduced by transposon delivery. Synthesis of recombinant HMW2 at wild-type levels resulted in reacquisition of hemadsorption and normal levels of HMW1, HMW3, and P65. Low-level production of HMW2 in some transformants resulted in only an intermediate capacity to hemadsorb. Furthermore, full restoration of HMW1 and P65, but not that of HMW3, was directly proportional to the amount of recombinant HMW2 produced, reflecting the importance of proper stoichiometry for certain cytadherence-associated proteins. The recombinant class I hmw2 allele did not restore cytadherence, consistent with a defect in hmw2 in this mutant. A frameshift was discovered in different oligoadenine tracts in hmw2 from two independent class I mutants. Finally, protein P28 is thought to be the product of internal translation initiation in hmw2. A transposon excision-deletion mutant produced a truncated HMW2 but no P28, consistent with this conclusion. However, this deletion mutant was hemadsorption positive, indicating that P28 may not be required for cytadherence.